Iron-induced changes in pyruvate metabolism of Tritrichomonas foetus and involvement of iron in expression of hydrogenosomal proteins - Vanácová, S; Rasoloson, D; Rázga, J; Hrdý, I; Kulda, J; Tachezy, J (Microbiology (Reading, England), 2001)
The main function of the hydrogenosome, a typical organelle of trichomonads, is to convert malate or pyruvate to H(2), CO(2) and acetate by a pathway associated with ATP synthesis. This pathway relies on activity of iron-sulfur proteins such as pyruvate:ferredoxin oxidoreductase (PFOR), hydrogenase and ferredoxin. To examine the effect of iron availability on proper hydrogenosomal function, the metabolic activity of the hydrogenosome and expression of hydrogenosomal enzymes were compared in Tritrichomonas foetus maintained under iron-rich (150 microM iron nitrilotriacetate) or iron-restricted (180 microM 2,2-dipyridyl) conditions in vitro. The activities of PFOR and hydrogenase, and also production of acetate and H(2), were markedly decreased or absent in iron-restricted trichomonads. Moreover, a decrease in activity of the hydrogenosomal malic enzyme, which is a non-Fe-S protein, was also observed. Impaired function of hydrogenosomes under iron-restricted conditions was compensated for by activation of the cytosolic pathway, mediating conversion of pyruvate to ethanol via acetaldehyde. This metabolic switch was fully reversible. Production of hydrogen by iron-restricted trichomonads was restored to the level of organisms grown under iron-rich conditions within 3 h after addition of 150 microM iron nitrilotriacetate. Protein analysis of purified hydrogenosomes from iron-restricted cells showed decreased levels of proteins corresponding to PFOR, malic enzyme and ferredoxin. Accordingly, these cells displayed decreased steady-state level and synthesis of mRNAs encoding PFOR and hydrogenosomal malic enzyme. These data demonstrate that iron is essential for function of the hydrogenosome, show its involvement in the expression of hydrogenosomal proteins and indicate the presence of iron-dependent control of gene transcription in Tt. foetus.
Keywords: pyruváty; Iron; ketonoxidoreduktasy; organely; zvířata; regulace genové exprese; protozoální proteiny; Gene Expression Regulation; Transcription, Genetic; cytosol; Pyruvates; malátdehydrogenasa; železo; Tritrichomonas foetus; Malate Dehydrogenase; Ketone Oxidoreductases; pyruvátsynthasa; Organelles; Cytosol; Animals; Protozoan Proteins; Pyruvate Synthase; genetická transkripce